Pembacaan Empat surah Pilihan dari Al-Qur’an dalam Tradisi Ngapati: (Studi Living Qur’an di Desa Trapung Raya Kecamatan Muara Batang Toru Kabupaten Tapanuli Selatan) - Bismaini Dongoran, Bismaini; Azmi Nasution, Muhammad Ali (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research is a living Al-Quran research that discusses the reading of four selected surahs in the Ngapati tradition in Trapung Raya Village, Muara Batang Toru Sub-district, South Tapanuli Regency. The method used in this research is field research with a qualitative method approach. The purpose of this research is to reveal the tradition and understanding of the recitation of selected surahs of the Qur'an in the Ngapati tradition which is carried out during pregnancy. The results showed that (1) the background of the recitation of four selected surahs in the Ngapati tradition is closely related to the Prophet's hadith about human creation. The ngapati tradition is carried out when the womb enters four months or 120 days, through the stages of opening and tawassul to the Prophet, which is then continued with salawat and reading selected surahs from the Qur'an. (2) The meaning contained in the reading of selected surahs of the Qur'an in the ngapati tradition can be understood from the community's view of surah Yasin, Yusuf, Maryam, and Luqman. The community's interpretation of the recitation of the four selected surahs includes: First, QS. Yusuf is believed to give hope that the child conceived can be born in perfect physical condition and become a good example in the future, there are several verses that are expected to be a guide. First, from QS. Maryam, it is hoped that we can emulate the steadfastness of Siti Maryam. This verse also provides peace for mothers not to feel anxious when facing the labor process, and hopes that the process will be made easier. Second, from QS. Al-Taubah, it is hoped that the conceived child will always be overwhelmed with a sense of repentance in the way of Allah swt. and have his sustenance widened and Fourth, QS. Luqman is seen as a hope for newborn babies to get good guidance. Thus, this study provides an in-depth insight into the ngapati tradition which is not only a ritual, but also a spiritual tool and hope for families awaiting the birth of a child.